Management of Academic Supervision to Improve Teacher Performance at MTsN 3 and MTsN 4 Banjarmasin City - Adnan, Adnan; Sujiarto, Heru; Iriantara, Yosal; Mulianai, Yenny (CV. Inara, 2022)
This study is motivated by low teacher performance at MTsN 3 and MTsN 4 Banjarmasin, such as: (a) the unpreparedness of the teachers in carrying out teaching, (b) a number of teachers do not have textbooks and do not arrange teaching units, (c) low basic skills, especially in evaluating learning processes. This study focused on 1) academic supervision policies and programs to improve teacher performance; 2) implementation of academic supervision policies and programs to improve teacher performance; 3) academic supervision problems to improve teacher performance; and 4) future solutions and improvements on the implementation of academic supervision to improve teacher performance at MTsN 3 and MTsN 4 Banjarmasin. This study used a qualitative approach with a case study method. Data were collected using interviews, observation, and document studies to then further analyzed using triangulation techniques. This study used management theory by Griffin and supervision theory by Daresh, and performance theory by Hersey & Blanchard. Based on the results; 1) academic supervision policies and programs were not optimal to improve teacher performance; 2) academic supervision policies and programs to improve teacher performance based on assessment aspects have been carried out, but administrative requirements for teacher performance appraisals have not been fulfilled; 3) implementation of academic supervision to improve teacher performance is faced with low mentality, infrastructure support, financing, and unclear division of academic supervision tasks, and 4) future solutions and improvements on implementation of academic supervision to improve teacher performance at MTsN 3 and MTsN 4 Banjarmasin is through providing clarity on planning, implementation, and evaluation of academic supervision to improve teacher performance. Thus, it can be concluded that the management of academic supervision to improve teacher performance has been carried out through management stages but is still not maximized to comply with national education standards.